If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1x + 3 = -2x + 1 Reorder the terms: 3 + -1x = -2x + 1 Reorder the terms: 3 + -1x = 1 + -2x Solving 3 + -1x = 1 + -2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2x' to each side of the equation. 3 + -1x + 2x = 1 + -2x + 2x Combine like terms: -1x + 2x = 1x 3 + 1x = 1 + -2x + 2x Combine like terms: -2x + 2x = 0 3 + 1x = 1 + 0 3 + 1x = 1 Add '-3' to each side of the equation. 3 + -3 + 1x = 1 + -3 Combine like terms: 3 + -3 = 0 0 + 1x = 1 + -3 1x = 1 + -3 Combine like terms: 1 + -3 = -2 1x = -2 Divide each side by '1'. x = -2 Simplifying x = -2
| 6[5x-(3x-1)]=4(3x-7) | | [-2+(-2)]+[3+(-1)]= | | X^3-3x^2+100=0 | | c=23.15r | | y=6(x+7) | | 7x-(8x+10)=x-13 | | -7.6r+5=-7.8 | | 1/3n=4 | | 3(-1)-7y=9 | | 6.3(-x-4)-7.7=-107 | | 5X-4=39+x | | Y-5/6=25/4 | | 9z=6(1/2z-5) | | 100(.166666)= | | 9(x-1)+33=x-8(x+1) | | -4e-6e+3e= | | -3x-7(-315-38x/63)=21 | | 14k+35=105 | | 5v/3=35 | | 8y(4-1)=2y-6 | | -36+3b=6b-2(5-5b) | | 7(1/4+c)=7/3 | | 2(y-2)-y=-2 | | 4/5(n)=9/10 | | 12-8x=8x+4 | | 3x/4+2=4x+1 | | 4(2x-7)+13=10x-15 | | 4u^2-11u-3=0 | | -2c=18 | | 4x-5-3x=5 | | -4x-1=-2x+5 | | 6x-6=18+9x |